Tricycles for Nigerian public transport unit: assessment of ergonomics design considerations - Hezekiah O, Adeyemi; Taofeek A, Yusuf (Penerbit Universiti Kebangsaan Malaysia, 2019)
Tricycles are becoming more popular commercial means of transport across all Nigerian cities. This study evaluated ergonomics status of this development. Measurement of seven variables comprising, seats’ height, width and cushion inclination as well as space available for legs, back rest inclination, access/exit doors and circulation corridors, were carried out on the sampled Tricycle. The measured variables were compared with both the standard recommended for urban transport unit and the corresponding anthropometric data of users from Southwest and Eastern parts of Nigeria (SW/EN). Data were collected from 175 passengers through questionnaire to measure the degree of comfort/discomfort derived using the transit unit. Microsoft Office Excel 2007 was used for statistical analysis. About 59% of the total passengers reported discomfort using Tricycle. Among these, 26.6% complained of strains at hips/upper legs, 22.9% neck pains and 21.0% knees/lower legs. More than 23% of the affected attributed this to lack of space for legs’ adjustment. All seats’ dimensions deviated from the required standard. The z-test result also showed significant differences for 87.5% of the total measured in-element parameters when compared with corresponding 95th anthropometric data of users from SW/EN. The study showed that passengers using Tricycles are susceptible to injuries connected with awkward postures, vibrations and external contact stress. Improving design with the recommended standards for urban transport, as suggested by the finding, may help in overtaking these challenges.